Targeted Molecular Imaging in Oncology - Kim, E. Edmund; Yang, David J. (Springer New York, 2001)
Cancer cells dedifferentiate with repect to cell function; their vascularity is more leaky, but perfusion is heterogenerously reduced, and interstitial fluid pressure is high, severely retarding delivery of agents from the blood. Targeted imaging is designed to produce a detectable difference between tissue that is visualized with single photon and positron emission tomography, magnetic resonance imaging, computed tomography, or ultrasonography. This book uniquely reports strategies for the application of molecular targeted imaging agents such as antibodies, peptides, receptors and contrast agents in the biologic grading of tumors, differential diagnosis of tumors, prediction of therapeutic response and monitoring tumor response to treatment. This book also describes updated information about the imaging of tumor angiogenesis, hypoxia, apoptosis and gene delivery as well as expression in the understanding and utility of tumor molecular biology for better cancer management
Keywords: Oncology; Nuclear Medicine; Oncology; Nuclear medicine; Bildgebendes Verfahren; Krebs -- Medizin; Diagnose